Solitary wave fission and fusion in the (2+1)-dimensional generalized Broer–Kaup system - Dai, Chaoqing; Liu, Cuiyun (Nonlinear Analysis: Modelling and Control, 2012)
Via a special Painlevé–Bäcklund transformation and the linear superposition theorem, we derive the general variable separation solution of the (2 + 1)-dimensional generalized Broer–Kaup system. Based on the general variable separation solution and choosing some suitable variable separated functions, new types of V-shaped and A-shaped solitary wave fusion and Y-shaped solitary wave fission phenomena are reported.
Keywords: variable separation solution; solitary wave fission and fusion, (2 1)-dimensional generalized Broer–Kaup system